Monitoring of the mangrove ecosystem in the province of Guayas-Ecuador during the period 2018-2022. - Caiza Morales, Lorena (2023)
Mangroves are highly productive ecosystems that provide important ecosystem services, are strategic allies in carbon capture and storage, conserve different plant and wildlife species, are producers of aquatic species such as crabs and shrimp, and local communities have developed strong economic, cultural and identity ties. Despite their great ecological, economic, and social importance, mangroves are threatened by natural and anthropogenic factors, hence the importance of their constant monitoring. Remote sensing technology has demonstrated its ability to map changes in mangroves and technological advances allow faster application of mapping methodologies, optimizing costs and time. To facilitate the sustainable management of mangroves, an open tool based on remote sensing data and machine learning was developed on the Google Earth Engine platform (MANGLEE). MANGLEE was tested in the mangroves of Guayas, Ecuador. Mangrove cover maps were obtained for the years 2018, 2020 and 2022 as well as the mangrove change maps for the two periods 2018-2020 and 2020-2022. The maps generated in this service are also available on the APP MANGLEE: The methodology and the diffusion workshops are available at the following link. The source code can be found in GitHub MANGLEE: This publication is possible by the support of the people of the United States through the United States Agency for International Development .(USAID). The content of this publication is the responsibility of its authors and does not necessarily reflect the views of USAID or the Government of the United States of America.